The Construction of Corporate Social Responsibility to Realize the Welfare of State - Dulman; Rachmad Budiono, Abdul; Permadi, Iwan; Syaufi , Achmad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to analyse and formulate the laws construction. Law construction of corporate social responsibility to realize the welfare of state. The effort is to increase the role of local governments in this era of regional autonomy, providing legal certainty in the form of agreements between the company and the public about the implementation of corporate social responsibility, where the role of notary in the creation of an agreement deed in realizing the company’s social responsibility is to translate the agreement that will be done by the parties and can accommodate the interests of the parties so as to Legally up to the realized definitive agreement, as well as required the existence of criminal law as a ultimumremidium, this is done through the criminalization of the company’s deeds that do not carry out corporate social responsibility and the application of criminal sanctions relevant to the company’s characteristics as a corporation